Tailored (Bio)Interfaces via Surface Initiated Polymerization: Control of Grafting Density and New Responsive Diblock Copolymer Brushes. Issue 1 (12th July 2013) - Lilge, Inga; Steuber, Marc; Tranchida, Davide; Sperotto, Elena; Schönherr, Holger; Kovačević, Vera
Summary Polymer brush synthesis by surface initiated polymerization (SIP) comprises a powerful strategy to tailor interfacial properties. Among others, the passivation of solid substrates against non‐specific protein adsorption or the implementation of stimuli responsive properties can be achieved. In this context controlled radical polymerization approaches are frequently employed. Here we report on our efforts in the synthesis of oligo and di(ethylene glycol) methylether methacrylate (OEGMA and DEGMA)‐based brushes with (i) controlled grafting density and (ii) new diblock copolymer structures. We assembled mixed self‐assembled monolayers (SAMs) comprising octadecanethiol (ODT), 16‐mercaptohexadecanoic (MHDA) and ω‐mercaptoundecyl bromoisobutyrate (MUBiB) on gold to initiate the controlled radical polymerization of OEGMA and DEGMA. The SAMs as well as the polymer layers obtained by atom transfer radical polymerization for a constant polymerization time were characterized by contact angle measurements with water, FTIR spectroscopy, ellipsometry and atomic force microscopy (AFM). It was found that ODT and MHDA assemble in the mixed SAMs preferentially and despite the different endgroups very similar brushes were obtained. SAMs with fractional surface coverages of the initiator ω‐mercaptoundecyl bromoisobutyrate of > 0.45 showed no further increase in brush thickness, which is in line with a mushroom to brush transition below this coverage. In addition, diblock copolymer brushes comprising POEGMA and poly(tert‐butyl acrylate) (PtBA) blocks were obtained for the first time. The PtBA block was successfully hydrolyzed to yield POEGMA‐block‐poly acrylic acid (PAA) brushes.